2021
DOI: 10.4274/atfm.galenos.2021.27879
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Children With Pseudotumor Cerebri: A Single Center Experience

Abstract: Psödotümör serebri intrakraniyal basınç artışı bulgularının gözlendiği, kafa içi yer kaplayan patolojilerin bulunmadığı nadir nörolojik bir durumdur. Çalışmamızın amacı psödotümör serebri tanısıyla takip edilen hastaların demografik özellikleri, tanı, tedavi ve prognozlarının tespit edilmesidir.Gereç ve Yöntem: Üçüncü basamak eğitim ve araştırma hastanesi çocuk nöroloji polikliniğinde Eylül 2017 -Mart 2019 tarihleri arasında psödotümör serebri tanısı ile takip edilen 15 hastanın (9 kız, 6 erkek) verileri retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A statistically signi cant positive correlation was observed between monocyte values and CSF pressure values. Previous studies on PTS reported that in general, there was no sex difference in the prepubertal period in childhood, but it was more prevalent in girls after puberty and among adults 1,11,12 . In this study, the mean age of our patients coincided with the pubertal period and consistent with the previous studies in the relevant literature, PTS was slightly more prevalent in female sex.…”
Section: Discussionmentioning
confidence: 80%
“…A statistically signi cant positive correlation was observed between monocyte values and CSF pressure values. Previous studies on PTS reported that in general, there was no sex difference in the prepubertal period in childhood, but it was more prevalent in girls after puberty and among adults 1,11,12 . In this study, the mean age of our patients coincided with the pubertal period and consistent with the previous studies in the relevant literature, PTS was slightly more prevalent in female sex.…”
Section: Discussionmentioning
confidence: 80%